2016
DOI: 10.1186/s40851-016-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

Mode of reduction in the number of pharyngeal segments within the sarcopterygians

Abstract: BackgroundPharyngeal segmentation is a defining feature of vertebrate embryos and is apparent as a series of bulges found on the lateral surface of the embryonic head, the pharyngeal arches. The ancestral condition for gnathostomes is to have seven pharyngeal segments: jaw, hyoid, and five posterior branchial arches. However, within the sarcopterygians, the pharyngeal region has undergone extensive remodelling that resulted in a reduction in the number of pharyngeal segments, such that amniotes have only five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Our recent studies have highlighted homologous features of the posterior limit of the pharyngeal arches across the vertebrates (Shone et al 2016). It has been shown that the most posterior pouch is marked by expression of HOX1.…”
Section: Evolutionary Considerations and Support For A '6th' Arch In mentioning
confidence: 96%
See 2 more Smart Citations
“…Our recent studies have highlighted homologous features of the posterior limit of the pharyngeal arches across the vertebrates (Shone et al 2016). It has been shown that the most posterior pouch is marked by expression of HOX1.…”
Section: Evolutionary Considerations and Support For A '6th' Arch In mentioning
confidence: 96%
“…It has been shown that the most posterior pouch is marked by expression of HOX1. Thus, in lampreys, it is the 8th pouch that expresses LjHox1w (Takio et al 2007), in the catshark the 6th pouch expresses HoxB1, and in amniotes, chick and mouse, it is the 4th pouch that expresses HoxB1 (Shone et al 2016). Additionally, in all vertebrates, the posterior margin of the pharynx is skirted by the hypoglossal (XIIth) nerve and the fourth pouch is the site of origin of the ultimobranchial body (Kardong, 2012;Shone et al 2016).…”
Section: Evolutionary Considerations and Support For A '6th' Arch In mentioning
confidence: 99%
See 1 more Smart Citation
“…Kishida et al (2015), for example, have demonstrated that baleen whales lost the dorsal domain of the olfactory bulb, known to induce innate avoidance behavior against odors of predators and spoiled foods, before the toothed and baleen whale split based on not only whole genome sequences but also fossil data, indicating that profound changes in the chemosensory capabilities had occurred in the cetacean lineage during the period when ancestral whales migrated from land to water. Shone et al (2016) evaluated fossil agnathan morphological traits to speculate about an evolutionary sequence in vertebrate gill number. Suzuki et al (2016) referred to placoderm fossil data (Young, 2008) in suggesting that vertebrate extrinsic eye muscles adhere to ancestral anatomical patterns.…”
Section: To Enhance Evolutionary Studiesmentioning
confidence: 99%
“…Hox genes are thought to play important roles in establishing the regional identity of the pharynx along the AP axis (Couly et al, 1998;Gendron-Maguire et al, 1993;Hunt et al, 1991;Rijli et al, 1993). In the pharyngeal endoderm, Hox genes also exhibit coordinated expression during vertebrate development (Shone et al, 2016). In mice, loss of Hoxa1 and Hoxb1 functions results in absence of the third pharyngeal pouch derivatives, such as the thymus and parathyroid (Rossel and Capecchi, 1999).…”
Section: Introductionmentioning
confidence: 99%